Structural phases, magnetic properties and Maxwell-Wagner type relaxation of CoFe2O4/Sr2Co2Fe12O22 ferrite composites - Patel, Chirag K.; Solanki, Neha P.; Singh, Charanjeet; Jotania, Rajshree B.; Chauhan, Chetna C.; Kulkarni, Shailja D.; Shirsath, Sagar E. (Materials Research Express, 2017)
CoFe2O4 (S:Y-1:0) and Sr2Co2Fe12O22 (S:Y-0:1) ferrites were synthesized separately by using chemical coprecipitation technique and calcined at 1000 degrees C for 5 h. The mixed ferrite composites (S:Y-3:7, 4:6, 5:5, 6:4 and 7:3) were prepared by physical mixing of individual ferrite powders in required weight proportions. The prepared composites were heated at 1150 degrees C for 5 h in a muffle furnace and then slowly cooled to room temperature. The prepared ferrites were characterized using various instrumental techniques like FTIR, XRD, SEM, VSM and dielectric measurements. The x-ray diffraction studies of pure Sr2Co2Fe12O22 ferrite sample show the presence of M and Y-type hexagonal phases, while the composites consist of spinel and Y-type phases. FTIR spectra of all samples show two bands of Fe-O stretching vibrations. VSM results of composites reveal that the values of the saturation magnetization (M-s) vary from 50.44 emu g(-1) to 31.21 emu g(-1), while remanent magnetization values found from 11.18 emu g(-1) to 3.70 emu g(-1). A higher value of coercivity (H-c = 562 emu g(-1)) is observed in the composite S:Y-3:7 but Mr/Ms ratio of pure and composites is found to be less than 0.5. The dielectric behavior is explained using Maxwell-Wegner type interfacial polarization and N. Rezlescu's model.